The fentanyl family: A distinguished medical history tainted by abuse. (4th October 2017) - Raffa, R. B.; Pergolizzi, J. V.; LeQuang, J. A.; Taylor, R.; ,; Colucci, S.; Annabi, M. H.
Summary: What is known and objective: Beginning in the 1950s, a family of potent opioids was synthesized and developed (fentanyl and analogues). They continue to serve as valuable analgesic agents. But the recent spike and notoriety of their abuse has raised alarm, even calls for tighter control. We review the trajectory of these compounds. Comment: To rectify shortcomings of the then available opioid analgesics, an analogue family of compounds was synthesized having a piperidine ring (presumptive principal active moiety in morphine and meperidine). The result was more potent and rapid‐acting compounds, including alfentanil, carfentanil, fentanyl, sufentanil and others. These properties, plus availability in formulations for multiple routes of administration, impart broad therapeutic utility. They also unfortunately favour abuse. What is new and conclusion: The abuse of fentanyl and its analogues (legal and illicit) serves as a case study for the dilemma and difficulties balancing a medical need against psychosocial realities. The fentanyl family provides relief for severe pain, but their very properties also engender abuse. Abstract : Chemical structures of morphine ( left ) and meperidine ( right ), highlighting the piperidine ring (dotted line).